2017
DOI: 10.2298/vsp150224257v
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcomes of new-onset atrial fibrillation in patients with acute myocardial infarction

Abstract: Background/Aim. The onset of atrial fibrillation (AF) in the acute phase of myocardial infarction (MI) may be a predictor of poor prognosis. The aim of our study was to examine this relationship. Methods. Six hundred patients were enrolled in the study and divided into two groups. The first group included 48 patients with new-onset AF and the second group of 552 patients without this arrhythmia. Patients with previously registered AF were excluded from the study. We investigated the correlation between new-ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Macrostructural disarray within the cardiac muscle due to fibrotic infiltration and disruptions of ionic currents and conductance at a cellular level predispose the infarcted heart to increased arrhythmic activity[36]. The incidence of atrial fibrillation (AF), one of the most prevalent arrhythmias encountered clinically, is estimated to be between 6–21% after MI[37], and is correlated with a higher mortality and adverse events during and after in-hospital period. Inflammatory mediators such as C-reactive protein (CRP), IL-6, and TNFα are elevated in AF, lending credence to I/R-associated inflammation as a possible etiology[38].…”
Section: Pathologic Signaling In Ischemic Heart Diseasementioning
confidence: 99%
“…Macrostructural disarray within the cardiac muscle due to fibrotic infiltration and disruptions of ionic currents and conductance at a cellular level predispose the infarcted heart to increased arrhythmic activity[36]. The incidence of atrial fibrillation (AF), one of the most prevalent arrhythmias encountered clinically, is estimated to be between 6–21% after MI[37], and is correlated with a higher mortality and adverse events during and after in-hospital period. Inflammatory mediators such as C-reactive protein (CRP), IL-6, and TNFα are elevated in AF, lending credence to I/R-associated inflammation as a possible etiology[38].…”
Section: Pathologic Signaling In Ischemic Heart Diseasementioning
confidence: 99%
“…1,2 Acute myocardial infarction (AMI) is a known risk factor for AF 3,4 and is an independent predictor of mortality in patients with AF. 5,6 Conversely, AF is an independent predictor of AMI, specifically non-ST-segment elevation myocardial infarction (NSTEMI). 7 9 Patients presenting with acute symptoms of AF, especially those with rapid ventricular response, may develop troponin elevations, which occur in 8% to 20% of patients with acute-onset AF.…”
Section: Introductionmentioning
confidence: 99%
“…In our study we observed that incidence of new onset of AF in MI patients is also associated with age, with passage of time risk of this incidence also increases. In a study conducted by Vukmirović M et al16 reported 6% incidence of AF after AMI and also reported that new onset of AF is associated with age. Arrhythmias are common in older age.…”
mentioning
confidence: 99%